Woodfordia fruticosa extract nanoemulsion: Influence of processing treatment on droplet size and its assessment for in vitro antimicrobial and anti-inflammatory activity - Najda, Agnieszka; Bains, Aarti; Klepacka, Joanna; Chawla, Prince (Frontiers in Nutrition, 2022)
Recently, plant-derived bioactive compounds can be utilized in the preparation of several functional food products, however, stability and water solubility are major constraints to these compounds. Therefore, to overcome this problem, the synthesis of nanoemulsion (oil in water) with varying concentrations of Woodfordia fruticosa flower extract (1-10% w/v) was carried out and evaluated for antimicrobial and anti-inflammatory activity. The average droplet size of nanoemulsion samples ranges from 154.42 to 221.34 nm. Based on the thermal stability (30-90℃), pH (2-9), and salt concentration (100-600 mM), the nanoemulsion sample with 3% extract showed stability for flocculation and coalescence, therefore, selected for further analysis. The sample showed remarkable antioxidant, anti-inflammatory as well as antimicrobial activity against Gram-positive Bacteria Staphylococcus. aureus, Gram negative bacteria Pseudomonas aeruginosa and fugal strain Candida albicans. Due to these biological activities, the WFNE3 nanoemulsion sample could be scaled up to the industrial level for the formulation of varied types of functional foods.